Effect of halliwick aquatic therapy and a land-based homologous program on postural control in children with cerebral palsy - Julio E Pérez-Parra; Yuli J Orejuela-Holguín; Jessica Maya-Álvarez; Juana Azuero-Losada (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: This study explores whether the effectiveness of Halliwick aquatic therapy is attributable to the mechanical properties of water, to the therapeutic exercise program developed during the sessions, or to a combination of both. This study aimed to determine the effect of Halliwick Aquatic Therapy and a homologous land-based program on postural control in children with cerebral palsy aged 5 to 15 years classified as GMFCS levels I, II, and III. Methods: A controlled clinical trial with a crossover design was conducted. Seventeen children participated, with a mean age of 9 years, most of them with hemiparesis. Each child received both interventions: Halliwick aquatic therapy and a land-based homologous program. The initial intervention was randomized. Postural control was assessed using the Pediatric Berg Scale and dimension E of the Gross Motor Function Measure. Analyses included intra- and inter-sample differences, as well as repeated measures ANOVA. Results: Balance improved significantly with both interventions (p<0.01). Gross motor function improved with both interventions but only reached significance on land (p<0.001). Significant differences were found in the improvement of balance between the interventions. (p=0.017), with greater improvement on land. The sequential application of both interventions significantly improved both balance (p<0.001) and gross motor function (p=0.013). Conclusions: The land-based program homologous to Halliwick Aquatic Therapy significantly improves gross motor function and balance in children with CP. A combined approach of consecutive therapies is recommended to optimize outcomes.